Taysir Batniji - Home away from home - Batniji, Taysir 1966-; Martin, Lesley A. ca. 20./21. Jh (Aperture Foundation, 2018)
Palestinian French artist Taysir Batniji is the third recipient of Immersion, a French American Photography Commission, a program launched by the Fondation d'entreprise Hermès in alliance with Aperture Foundation. In Home Away from Home , Batniji brings together photographs, selections from family archives, drawings, and writings to explore the sense of dislocation and the different ideas of home experienced by various members of his family who immigrated to the United States from the Middle East. As Batniji explains, The state of between-ness cultural as well as geographic is an issue that has preoccupied me since I first arrived in France in 1995. Exile, displacement, and mobility are themes that have driven my work for many years. Exhibition: Aperture Gallery, New York, USA (15.03.-10.05.2018) / Rencontres d'Arles, France (02.07.-23.09.2018)
"A Foundation d'entreprise Hermès book, published by Aperture, on the occasion of the exhibition Home Away from Home at Aperture Gallery, March 15-May 10, 2018."--Colophon
"The works presented here are the result of journeys I made in 2017, to Florida [...] and to California...."--Artist's statement page, opposite title page verso
Keywords: Batniji, Taysir -- 1966-; Fotografie; Heimatlosigkeit -- Motiv; Exil -- Motiv; Zuhause -- Motiv; Palästinenser -- Motiv; Batniji, Taysir 1967- / Exhibitions; Batniji, Taysir 1967- / Exhibitions / Travel / Florida; Batniji, Taysir 1967- / Exhibitions / Travel / California / Batniji, Taysir 1967- / 2000-2099; Arabs / Exhibitions / United States; Palestinian Arabs / Exhibitions / United States; Photography, Artistic / Exhibitions / 21st century; Photography, Artistic; Arabs; Palestinian Arabs; Travel / United States / California / Florida; Ausstellungskatalog -- Aperture Gallery -- 15.03.2018-10.05.2018 -- New York, NY; Bildband